2011 First SysSec Workshop 2011
DOI: 10.1109/syssec.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

CAPTCHuring Automated (Smart) Phone Attacks

Abstract: Abstract-As the Internet has entered everyday life and become tightly bound to telephony, both in the form of Voice over IP technology as well as Internet-enabled cellular devices, several attacks have emerged that target both landline and mobile devices. We present a variation of an existing attack, that exploits smartphone devices to launch a DoS attack against a telephone device by issuing a large amount of missed calls. In that light, we conduct an excessive study of Phone CAPTCHA usage for preventing atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…We found Math-function captcha performed better than alphabet captcha, contrary to the existing work [11]. We found that alphabet captcha's accuracy was comparable to numeric captcha.…”
Section: Discussioncontrasting
confidence: 90%
“…We found Math-function captcha performed better than alphabet captcha, contrary to the existing work [11]. We found that alphabet captcha's accuracy was comparable to numeric captcha.…”
Section: Discussioncontrasting
confidence: 90%